Effect of ferrocene concentration on the quality of multiwalled CNTs grown by floating catalytic chemical vapor deposition technique - Shukrullah, S. (IOS Press, 2014)
Controllable synthesis of quality carbon nanotubes is a precondition for their broad applications. The objective of the work was to study the effect of catalyst concentration on the quality, diameter, length, alignment and crystallinity of the grown multiwalled carbon nanotubes (MWCNTs). To meet the stated objective, MWCNTs were successfully synthesized by using floating catalytic chemical vapor deposition technique. The ferrocene concentration was varied from 0.1 to 0.2 g and MWCNTs were synthesized with ethylene as a carbon precursor at reaction temperature of 850Â°C. The grown MWCNTs were characterized by using scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Raman spectroscopy. The obtained data revealed that an increase in concentration of the ferrocene significantly affects the diameter, crystallinity and growth of nanotubes, however, negligible effect on the CNTs forest length was noticed. The dense, uniform and meadow like patterns of grown CNTs were observed for 0.15 g ferrocene. The average diameter of the grown CNTs was ranged from 32-75 nm. Above 0.15 g ferrocene, some of the grown CNTs were found defective and few black spots were also appeared in TEM images. Â© 2014 IOS Press and the authors. All rights reserved.